2021
DOI: 10.3390/ma14216725
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Process and Microstructure Examination of Flux-Cored Wire Arc Additive Manufactured 18Ni-12Co-4Mo-Ti Maraging Steel

Abstract: The production of large-size elements using additive manufacturing is a constantly evolving field that includes technological and material solutions. There is a need for a detailed analysis of the process and the products thus manufactured. In line with this trend, the flux-cored wire arc additive manufactured process and the part made of 18Ni-12Co-4Mo-Ti maraging steel were examined. The interpass temperature below 150 °C, the variation of the starting point and the gas flow of 12 L/min with a pre-flow of 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Martensitic cellular structures or austenite on the cell borders might serve as 'bridges. 'for connection between the each and increase fracture resistance [69,[92][93][94][95][96][97]. The evolution of characteristics of maraging steel is greatly influenced by ageing.…”
Section: Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…Martensitic cellular structures or austenite on the cell borders might serve as 'bridges. 'for connection between the each and increase fracture resistance [69,[92][93][94][95][96][97]. The evolution of characteristics of maraging steel is greatly influenced by ageing.…”
Section: Porositymentioning
confidence: 99%
“…Similarly, anchor rails, arresting hooks [123], and gimbal ring parts are used in aerospace [138] and aircraft applications [92]. Maraging steel is also used in defense-related applications like cannon recoil springs [93], and lightweight portable military bridges. Apart from this, maraging steel is used in applications like car parts (frames) , and atomic power plant parts like rotors, and shafts [94].…”
Section: Application Of Maraging Steelsmentioning
confidence: 99%
“…wide range. The advantages of WAAM, as applied to maraging steels, [1][2][3] largely relate to higher production rates, but the structure and surface finish tend to be relatively coarse, and the porosity level can be high. In general, the LPBF technique has been more popular than WAAM for maraging steels, [4][5][6][7][8][9][10] offering superior scope for geometrical and microstructural control.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is partially solved by the application of Fronius Cold Metal Transfer technology, nevertheless that technology is patented, expensive and excludes other current sources [ 31 , 32 , 33 , 34 ]. Another approach is to introduce an additional cooling subsystem [ 35 ], yet that can result in unwanted changes in the microstructure [ 36 , 37 ], although Reisgen et al reported that they observed no negative effects [ 38 ].…”
Section: Introductionmentioning
confidence: 99%